Fair value and the subprime crisis: Does fair value accounting account for systemic failure of banking sector? - Yi, Feng (2009)
Fair value accounting has stimulated growing debate amount practitioners and academics under ongoing financial crisis. It is augured that fair value accounting result in strong mutually reinforcing pro-cyclical effects, provoking negative contagion in financial markets. This dissertation is aimed to investigate the impact of fair value accounting on the systemic risk of banking industry. Since the exploratory study of fair value and banks failure is in early stage, such a study will provide further empirical evidence on fair value accounting’s contribution to the crisis. This research will be implemented through an in-depth review of relevant literature and a critical analysis of empirical data. Based on Khan (2009)’s model, the study finds and confirms that a bank is more likely to bear extreme adverse return when money center banks are undergoing financial difficulties, and a more fair value oriented accounting regime is liable to an increase in systemic risk in the banking sector. The dissertation concludes that fair value accounting might be more than a bad news carrier but has contributed to the acceleration of financial crisis. The dissertation recommends the use of more sophisticated model taking into account other influencing factors and the need to expanding the study area for longer time series research.